Adapting web images for blind people - Misman, Ahmad Fatzilah; Blanchfield, Peter (2011)
One way to remedy the gap that evidently exists between the image element on the web and the web user who is visually blind is by redefining connection between the image and the abundant element of the web itself i.e. text. Studies on the exploitation are done largely related to the fields like the HCI, the semantic web, the information retrieval or even a new hybrid approach. However, often many see the problem from the perspective of the third party. This position paper posits that the problem can also be seen from the fundamental reasons for an image being on a web page without neglecting the connection that develops from the web user's perspective. Effective and appropriate image tagging may consider this view.